Prince of Persia the sands of time - Bruckheimer, Jerry; Arterton, Gemma; Gyllenhaal, Jake, 1980-; Molina, Alfred, 1953-; Kingsley, Ben, 1943-; Newell, Mike, 1942-; Mechner, Jordan; Yakin, Boaz.; Miro, Doug.; Bernard, Carlo; Walt Disney Pictures; Jerry Bruckheimer Films; et al. (Burbank, Calif. : Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
It's a race against time when a rogue prince (Jake Gyllenhaal) reluctantly teams up with a rival princess (Gemma Arterton) to safeguard a magical dagger that gives its possessor the power to reverse time and rule the world.
Widescreen.
Originally released as a motion picture in 2010.
Based on the video game series "Prince of Persia" created by Jordan Mechner.
Special features: An unseen world: making "Prince of Persia".
Director of photography, John Seale ; editors, Michael Khan, Mick Audsley, Martin Walsh ; music, Harry Gregson- Williams.
Jake Gyllenhaal, Ben Kingsley, Gemma Arterton, Alfred Molina.
Keywords: Princes -- Iran -- Drama; Princesses -- Drama; Time travel -- Drama; Iran -- Drama; Action and adventure films; Films for the hearing impaired; Feature films